Biostratigraphy and correlation of the Monte Hermoso Formation (early Pliocene, Argentina): the evidence from caviomorph rodents. - Deschamps, Cecilia Marcela (2012)
The Monte Hermoso Formation (Farola Monte Hermoso, Buenos Aires Province, early Pliocene) is very important because it is the type locality of biostratigraphic units of the South American mammal bearing Pliocene. These deposits were the base for the recognition of the Montehermosan and Lower Chapadmalalan stages/ages. The correlation of this unit, especially with the Chapadmalal Formation has been debated. Over the last twenty years, major improvements have been made in the knowledge of caviomorph rodents collected in the Monte Hermoso Formation. The results include information about systematics and morphological change within lineages of the families Echimyidae (incl. Myocastoridae), Ctenomyidae, Octodontidae, and Hydrochoeridae. This information allows refinement of biostratigraphic correlation with other localities of south-eastern Buenos Aires Province. First and last records, as well as evolutionary patterns of some lineages, suggest an important change between the faunas from the Monte Hermoso Formation (including Lithostratigraphic Units I and II) and the Chapadmalal Formation, rejecting the previously suggested similarity of the upper levels of the Monte Hermoso Formation (Unit II, Lower Chapadmalalan) with those of the Chapadmalal Formation (Upper Chapadmalalan). Studies of more lineages including new revisions are necessary to test this proposal.